Analisis Hukum dalam Penggunaan E-Materai di Kantor Notaris/Pejabat Pembuat Akta Tanah (PPAT) - Aji Anella Amayaffa; Deny Slamet Pribadi; Khristyawan Wisnu Wardana (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study focuses on the analysis of legal studies in the use of e-stamps in notary offices/land deed making officials (PPAT). This study aims to determine how the use of e-stamps in authentic deeds made before a notary/PPAT and how legal protection is provided for e-stamp users in notary/PPAT offices. This study uses a doctrinal approach which is a type of legal research on a collection of written norms/regulations and other secondary legal materials. The results obtained from this study are, first, that documents affixed with e-stamps are perfect evidence if used as evidence at a conference, the existence of e-stamps does not affect the validity of civil documents, only the authentic evidentiary force is degraded to a private deed due to the prohibition as stipulated in Article 5 paragraph (4) letter b of the ITE Law. Second, legal protection if the disputed document can be preventive, namely education and socialization related to the use of e-stamps in authentic deeds and repressive, namely providing protection to buyers as victims related to lawsuits for the Cancellation of certificates issued due to legal defects related to e-stamps sold to the State Administrative Court.